2017
DOI: 10.1038/ijo.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

The rise and the recent decline of childhood obesity in Swedish boys: the BEST cohort

Abstract: This long-term study captures both the rise and the recent decline of childhood obesity. As childhood obesity is strongly associated with subsequent adult obesity, we anticipate a similar reduction in adult obesity during the coming decades in Swedish men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
6
22
1
Order By: Relevance
“…Awareness of this potential risk may contribute to the higher burden among parents of overweight/obese children in the study. Nevertheless, the proportion of children with overweight/obesity is similar to that found in the general population in the same age range (Bygdell et al, ). Further studies are needed to explore the impact of overweight/obesity on perceived parental burden for parents of children affected with haemophilia.…”
Section: Discussionsupporting
confidence: 80%
“…Awareness of this potential risk may contribute to the higher burden among parents of overweight/obese children in the study. Nevertheless, the proportion of children with overweight/obesity is similar to that found in the general population in the same age range (Bygdell et al, ). Further studies are needed to explore the impact of overweight/obesity on perceived parental burden for parents of children affected with haemophilia.…”
Section: Discussionsupporting
confidence: 80%
“…The age interval of the present cohort was 52–68 years at the end of follow-up (December 31, 2013) and thus stroke risk later in life could not be studied. It should be emphasized that since the present cohort was born in 1945–1961, the prevalences of obesity are lower (1.3% at 8 years of age and 0.9% at 20 years in the present study), while the corresponding figures in more recent years are higher, 7.9% at 8 years of age 28 and 3.8% at age 20 in a study from the military service conscription register. 29 Thus the present study predates the childhood obesity epidemic and today's obesogenic environment may further enhance the observed associations with adult stroke events.…”
Section: Discussioncontrasting
confidence: 66%
“…There was an inverse association between childhood BMI and age at PHV in the present study population born 1947 to 1996 below, but not above, a threshold at 17.71 (eFigure 3 in the Supplement ). Given that childhood BMI increased during the same period, 11 we next wanted to determine the secular trend of earlier age at PHV independent of childhood BMI . When we included age at PHV and childhood BMI (median, 15.8; range 12.3-29.2) in the same linear regression model, we found that the association between birth year and age at PHV was slightly attenuated but remained significant; the age at PHV was 1.2 months earlier per decade increase during the study period (−0.10 years per decade increase in birth year; 95% CI, −0.12 to −0.07; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… 10 Moreover, we have reported a pronounced increase in mean childhood BMI among 8-year-old boys from the 1940s until now. 11 Here, we address the earlier mentioned knowledge gap regarding male pubertal timing and hypothesize that there is a secular trend for earlier pubertal timing in boys that can be partially explained by childhood BMI. This study’s aim was to investigate the association between birth year and changes in male pubertal timing independent of changes in childhood BMI.…”
Section: Introductionmentioning
confidence: 89%